Comparison of the physicochemical characteristics of fermented and centrifuged processed virgin coconut oil - Saavedra, Dande T.; Lizada, Ma. Concepcion C. (2006)
ABSRACT The physico-chemical properties of fermented and centrifuged virgin coconut oil were determined. The fermented sample had higher free fatty acids (11% as lauric) compared to the centrifuged sample (2.0% as lauric), indicating a greater degree of lipolytic degradation during the prolonged fermentation of 36 to 48 hours. Conversely, the low total volatile fatty acid (0.31%) for the fermented oil relative to that measured for the centrifuge oil (6.12%) provides further evidence that the frementation leads to more chemical changes where the liberated volatile fatty acids are likely to remain in the aqueous extract and lost to the oil. The greater resistance to flow observed in the fermented samples (8.33 sec/ml), compared to that in the centrifuged oil (7.34 sec/ml) would be consistent with the latter sample retaining more of the volatile fatty acids in triglycerides. The comparable moisture content of the two samples is difficult to explain on the basis of differences in the processes involved. However, the low moisture content of the fermented sample would be consistent with the possibility that it has been subjected to a treatment which reduces moisture, e.g. heating.
Thesis (BSFT)--University of the Philippines, Diliman.
Keywords: Virgin coconut oil